2021
DOI: 10.21307/sjcapp-2021-018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on height, weight and blood biochemistry parameters in prepubertal boys with attention deficit hyperactivity disorder: an open label prospective study

Abstract: Background: Adverse effects of stimulants on growth in children have long been studied, but the results remain to be clarified, because metabolic changes or predictors accompanying the growth deviations were not sufficiently studied. Objective: This open label-prospective study investigated the effects of methylphenidate (MPH) on weight, height, blood biochemistry in children with attention deficit hyperactivity disorder (ADHD). Method: Prepubertal boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
1
0
3
Order By: Relevance
“…A Tricotilomania também se caracteriza como um impulso de "Tique" em arrancar/puxar fios de cabelo do couro cabeludo e em cílios 21 . Irritabilidade, nervosismo e agitação também se apresentaram como efeitos adversos ao uso de metilfenidato 4,25,26 e podem estar associados com quadros de "tiques" e movimentos involuntários.…”
Section: Segundo O Manual Diagnóstico E Estatístico Deunclassified
See 2 more Smart Citations
“…A Tricotilomania também se caracteriza como um impulso de "Tique" em arrancar/puxar fios de cabelo do couro cabeludo e em cílios 21 . Irritabilidade, nervosismo e agitação também se apresentaram como efeitos adversos ao uso de metilfenidato 4,25,26 e podem estar associados com quadros de "tiques" e movimentos involuntários.…”
Section: Segundo O Manual Diagnóstico E Estatístico Deunclassified
“…A redução do apetite é um efeito colateral associado ao uso do Metilfenidato 4,5,21,22,24-27 e está diretamente relacionada com a perda de peso, incômodos estomacais e algia abdominal 4,21,22,24,27,28 . Outros sintomas como náuseas, emagrecimento, boca seca, gosto amargo na boca, sensação de intensificação do metabolismo corporal, sensação de fraqueza e cansaço estão associados com perda do apetite e do desenvolvimento da estatura 4,21,22,24 .…”
Section: Inapetência Perda De Peso Alopecia E Alterações Nos Parâmetr...unclassified
See 1 more Smart Citation
“…In the last 40 years, there has been a debate whether psychostimulants—specifically methylphenidate—affect growth in children who use them. Some studies have shown that these medications may affect the child’s weight at the start of treatment [ 12 , 14 , 15 , 16 ] and possibly affect height in the range of 1 to 2 cm after longer-term therapy [ 17 , 18 , 19 , 20 , 21 ]. Other studies have reported that height is affected by higher doses of psychostimulants [ 22 , 23 ], more so in those who start treatment before puberty [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%